Management of primary hypothyroidism: statement by the British Thyroid Association Executive Committee - Okosieme, Onyebuchi; Gilbert, Jackie; Abraham, Prakash; Boelaert, Kristien; Dayan, Colin; Gurnell, Mark; Leese, Graham; McCabe, Christopher; Perros, Petros; Smith, Vicki; Williams, Graham; Vanderpump, Mark (Clinical endocrinology (Oxford), 2016)
Summary The management of primary hypothyroidism with levothyroxine (L‐T4) is simple, effective and safe, and most patients report improved well‐being on initiation of treatment. However, a proportion of individuals continue to suffer with symptoms despite achieving adequate biochemical correction. The management of such individuals has been the subject of controversy and of considerable public interest. The American Thyroid Association (ATA) and the European Thyroid Association (ETA) have recently published guidelines on the diagnosis and management of hypothyroidism. These guidelines have been based on extensive reviews of the medical literature and include sections on the role of combination therapy with L‐T4 and liothyronine (L‐T3) in individuals who are persistently dissatisfied with L‐T4 therapy. This position statement by the British Thyroid Association (BTA) summarises the key points in these guidelines and makes recommendations on the management of primary hypothyroidism based on the current literature, review of the published positions of the ETA and ATA, and in line with best principles of good medical practice. The statement is endorsed by the Association of Clinical Biochemistry, (ACB), British Thyroid Foundation, (BTF), Royal College of Physicians (RCP) and Society for Endocrinology (SFE).